Double-Ring Sign to Confirm Correct Orientation of Donor Lenticules During Descemet Stripping Automated Endothelial Keratoplasty. Issue 8 (August 2015) - Delfazayebaher, Siamak; Feizi, Sepehr; Javadi, Mohammad Ali; Baradaran-Rafii, Alireza; Sadoughi, Mohammad Mehdi; Faramarzi, Amir
Abstract : Purpose: To describe a sign that can confirm the correct position of donor lenticules during Descemet stripping automated endothelial keratoplasty (DSAEK). Methods: In this clinical and laboratory study, DSAEK was performed in 3 eyes with a diagnosis of pseudophakic bullous keratopathy. Additionally, 2 whole globes and 2 precut corneoscleral buttons were procured for the purpose of the laboratory part of the study. After removal of recipient Descemet membrane, the donor graft was inserted into the anterior chamber, unfolded, and attached to the posterior corneal stroma with an air bubble. A similar procedure was performed in the eye-bank eyes with lenticules attached in both correct and upside-down orientations. Results: After the anterior chamber was completely filled with air, 2 or more concentric shiny rings were formed at the border of the donor lenticule because of total internal reflection in the graft. In the live and eye-bank eyes with a donor graft attached in the correct orientation, the innermost shiny ring, indicating the stromal side of the graft, was observed under the recipient cornea, whereas the outermost ring, indicating the endothelial side, was formed deeper. When the donor lenticule was intentionally implanted upside down in the eye-bank eyes, the reverse situation occurred, and the largest ring was observed just beneath the recipient cornea. Conclusions: The correct anterior–posterior orientation of the donor lenticule during DSAEK could be identified by the shiny rings formed at the border of the graft after the anterior chamber was completely filled with air. Abstract : Supplemental Digital Content is Available in the Text.